PERANCANGAN APLIKASI PERHITUNGAN ZAKAT MAL, MENENTUKAN WAKTU SHALAT DAN ARAH KIBLAT MENGGUNAKAN GPS BERBASIS ANDROID - Yasmin Dara; Denny Kurniadi; Khairi Budayawan (Universitas Negeri Padang, 2014)
The daily prayers are an important thing that should be done by every moslem in this world. One of the priorities in praying is to pray on the right time with directed to mecca Nowadays, most of moslem tend to neglect the time to pray as they are busy of their works. At this time, a moslem have to be discipline in splitting the time to do shalat. Those who earn and have enough income is supposed to pay the Zakat Mal according to the amount of their income. In this modern era, handphone has been used by the people in facilitating their works in daily life, because handphone have many functions out of its main function. Android is an operation system that is inserted into handphone which has function to help the user in installing the application that they need. In this final project, the writer proposed a title “The designing of application in calculating Zakat Mal, Determining the Time of Shalat, and Direction to Mecca by using GPS with android system base. This application will remind the user of the time of shalat and show the direction to Mecca that is supported by GPS system. This application also includes the menu for calculating the Zakat Mal. Keywords: Android Application, Zakat Mal, Shalat time, Direction of Kiblat. GPS (Global Position System)